Biomarking Study of Aromatic Hydrocarbon Fraction Crude Oil Tarakan, North Kalimantan - Rafwan Year Perry Burhan; Abduh Muharram Chairacita; Yulfi Zetra; Endah Mutiara (Jurnal Teknik ITS, 2019)
The study of the aromatics of aromatic hydrocarbons from Tarakan crude oil, North Kalimantan, has been carried out through the analysis of Gas Chromatography-Mass Spectroscopy (GC-MS) analysis. The biomarkers identified showed the presence of naphthalene groups, phenanthrene and pentacyclic triterpenoids where the pentacyclic triterpenoid showed the highest abundance. The presence of 3,3,7-trimethyl-1,2,3,4-tetrahydrochrysene biomarkers; 1,2,9-trimethyl-1,2,3,4-tetrahydropicene; 2,7-dimethyl-1,2- (isopropylpenteno) -1,2,3,4-tetrahydrochrysene and dinorursa-1,3,5 (10), 13 (18) -tetraene as indicators of plants Angiosperms and chrysene indicate input bacteria. The existence of 1,3,7 + 2,6,9 + 2,7,9-TMP biomarkers; 3-MC and 2-MC indicate mature oil samples. The presence of DMP, TMP and chrysene biomarkers indicates terrestrial and marine depositional environments.